Motor development in the first year of life predicts impairments in cognition and language at 3 years old in a Brazilian preterm cohort of low-income families - Panceri, Carolina; Silveira, Rita C.; Procianoy, Renato Soibelmann; Valentini, Nadia Cristina (Frontiers in Neuroscience, 2022)
Purpose: Early identification of impairments is crucial to providing better care for preterm children, especially those from low-income families. The early motor assessment is the first step in monitoring their neurodevelopment. This study investigates if motor development in the first year of life predicts impairments in cognition and language at 3-year-old in a Brazilian preterm cohort. Methods: Data were collected in a follow-up clinic for high-risk infants. The Bayley Scales were used to assess children at 4, 8, 12, and 36 months of age, considering composite scores. Cognitive and language impairments were considered if scores were ≤ 85. Children (N = 70) were assessed at 4 and 36 months, 79 were assessed at 8 and 36 months, and 80 were assessed at 12 and 36 months. Logistic regressions were used to analyze the predictability of cognitive and language impairments, and receiver-operating characteristics curves were used to analyze the sensibility and specificity of motor assessment and cognitive and language impairments. Results: Poor motor scores at 8 and 12 months increased the chances of cognitive and language impairment at 3-year-old. The chance of cognitive impairment at 3-year-old increases by 6 to 7% for each point that the motor composite score decreases, and the chance of language impairment at 3-year-old increases by 4 to 5% for each point that the motor composite score decreases. No-significant results were found at 4-months. Adequate sensibility and specificity were found for language impairments considering 12 months scores and for cognitive impairments as soon as 8 months scores. Conclusions: Monitoring preterm motor development in the first year of life helps to identify preterm children at risk for impairment in other developmental domains. Since preterm children from low-income families tend to demonstrate poorer neurodevelopment outcomes, these children need early assessment and referral to intervention to prevent school failures and support from public policies.